Low Quality Image Information Enhancement Using SVD Fusion Technique (International Journal of Engineering and Computer Science, 2013)
Images fusion technique based on Singular Value Decomposition (SVD) has been done on the blurred images with different level of blurring. The blurring of the image was done using circular averaging technique. Five different set of images were taken and on these images SVD based fusion implemented on the images. The content of the image were calculated with respect to reference image on the blurred image and fused image. PSNR value for highest blurred image come out to be for blurred and fused image 13.27 dB and 12.61 dB respectively. SNR value for blurred image is -10.85 and fused image -11.51. Image quality is enhanced by SVD fusion technique.